Techno Economic Study of Portable Hotel Construction Model and Alternatives Comparison Using The Hierarchical Analysis Method AHP - جنود علي (Latakia University Journal -Engineering Sciences Series, 2020)
The reconstruction phase requires capacity development and skills development in all construction institutions involved in the reconstruction process and the development of their technologies and equipment in preparation for this stage. Therefore, we present in this research new models of residential and service buildings that contributed to the settlement of displaced families as a result of the unjust war suffered by the Syrian Arab country. This research aims to apply and use the partial prefabricated system that consists of a metal structure and pre-made tiles (the mobile hotel) and to make an economical technical comparison of the hotel’s mobile model between the prefabricated and molded in the place. We show the main advantages and disadvantages of pre-made concrete in the construction, as well as clarify the advantages and disadvantages of cast concrete and partially pre-made concrete.A comparison was made between the aforementioned three alternatives using the hierarchical analysis method and the Expert choice program according to a set of criteria (technical, economic, aesthetic and sustainability) to choose the best building method for the hotel mobile model.